2015
DOI: 10.1158/0008-5472.can-14-1356
|View full text |Cite
|
Sign up to set email alerts
|

p21 Ablation in Liver Enhances DNA Damage, Cholestasis, and Carcinogenesis

Abstract: Genetic mouse studies suggest that the NF-kB pathway regulator NEMO (also known as IKKg) controls chronic inflammation and carcinogenesis in the liver. However, the molecular mechanisms explaining the function of NEMO are not well defined. Here, we report that overexpression of the cell-cycle regulator p21 is a critical feature of liver inflammation and carcinogenesis caused by the loss of NEMO. NEMO Dhepa mice develop chronic hepatitis characterized by increased hepatocyte apoptosis and proliferation that cau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…5A and B). Consistent with the FACS data, the expression of G1/S phase checkpoint proteins, including tumor suppressor p53 (P53) (34), cell cycle regulator p21 (P21) (35) and plasminogen activator inhibitor 1 (PAI-1) (36) were markedly upregulated in the cells infected with LV-RP5-833A20.1 (Fig. 5C).…”
Section: Rp5-833a201 Inhibits Cell Cycle Progression and Induces Celsupporting
confidence: 83%
“…5A and B). Consistent with the FACS data, the expression of G1/S phase checkpoint proteins, including tumor suppressor p53 (P53) (34), cell cycle regulator p21 (P21) (35) and plasminogen activator inhibitor 1 (PAI-1) (36) were markedly upregulated in the cells infected with LV-RP5-833A20.1 (Fig. 5C).…”
Section: Rp5-833a201 Inhibits Cell Cycle Progression and Induces Celsupporting
confidence: 83%
“…26 In papillomas, NF-κβ and the axis of ROCK2/FAK/β-catenin 5,6 may contribute to the demise of p53, given both NF-κβ 26 and FAK-associated β-catenin 38,46 inhibit p53 expression. These papilloma data thus link NF-κβ with increased DNA mutations/chromosomal instability 25,39 following p53 loss and associated p21 inhibition 47 [below]; and indirectly link ROCK2-mediated NF-κβ to stromal remodelling 25 thus accounting for effects previously observed on expression of ECM molecules such as tenascin C. 48,49 One consequence of p53 loss leading to an altered matrix may involve downregulated microRNAs, 34 such as miR-200 which regulates cell-cell adhesion molecules 35 and effected ROCK signalling in gastric cancer. 36 Of note, p53-mediated miR-200 expression depended upon AKT levels, 37 consistent with p53 loss driving malignant conversion in trigenic HK1.ras/fos/Pten flx carcinogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…This latter result not only shows the requirement for ROCK er -mediated NF-κβ expression to facilitate progression, but also demonstrated that p21 responses eliminated NF-κβ expression independent of ROCK2 signalling. 44,47 Furthermore, down-regulation of NF-κβ paralleled increasing basal layer p53 expression 26 which restored the p21/p53-mediated resistance to malignant conversion. 20,23 Indeed, this direct p21-mediated antagonism to NF-κβ signalling was recently demonstrated in liver carcinogenesis where p21 knockout was shown to be pivotal to progression following loss of NEMO, a major NF-kβ pathway regulator.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the best-known p53 target genes is p21, which regulates cell survival [36] and protects cells against apoptosis [37]. Western blot analysis showed a time-dependent expression of the KLK6, p21, and p53 levels after AF treatment in NCI-N87 and SNU-620 cells when compared to AF-sensitive cells, suggesting a role for these proteins in AF-induced cell death (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%